Perceptions on justice, the judiciary and democracy - Filgueiras,Fernando (2013)
The reliance on courts for addressing public policy questions and political controversies is a central phenomenon in contemporary democracies. The judicialization of politics is the result of a shift in core issues regarding democratic legitimacy, both in the sphere of institution building as well as political culture. Social justice arose as a central variable in the legitimacy of democracies, becoming vital in establishing support towards democratic political systems. This article explores the relation between perceptions on justice, judicialization of politics and how the agency of judicial institutions impacts dissatisfaction with democracy. Based on a survey carried out in the metropolitan regions of Belo Horizonte, Goiânia, Porto Alegre and Recife, it is argued that the discontent towards political institutions in Brazil does not justify the ongoing judicialization process since the perceptions on inequalities place the Judiciary within the citizens' critical stance towards institutions. Just like other representative institutions, the Judiciary has not been able to mitigate the perceptions on inequalities and the ineffectiveness of the empire of law, being therefore unable to provide a satisfactory performance in regards to the normative ends of contemporary notions of democratic legitimacy and citizenship.